Reflexivity Conducting Mixed Methods Research on Indigenous Women's Health in Lower and Middle-Income Countries - An Example From Bangladesh. (7th June 2022) - Akter, Shahinoor; Rich, Jane Louise; Davies, Kate; Inder, Kerry Jill
Indigenous women's health in low and middle-income countries continues to experience exclusions from the mainstream context and has remained underrepresented in health research, including qualitative research. Based on mixed methods research (comprising qualitative and quantitative methods) into Indigenous women in Bangladesh, this article addresses the reflexivity of a non-Indigenous researcher studying Indigenous women's health issues in the Chittagong Hill Tracts of Bangladesh. As reflexivity is a crucial strategy to ensure rigor in qualitative research, understanding how the characteristics and experiences of the study may influence the research process is of paramount importance. For non-Indigenous researchers working in an Indigenous context, the imperative to understand one's impact and position within the research becomes even more critical. Unfortunately, non-Indigenous researchers often avoid providing appropriate detail on reflexivity aspects in conducting research, particularly mixed-method research, among Indigenous communities in low- and middle-income countries like Bangladesh. In this reflexive evaluation, the researchers of this mixed method study evaluate the introspective reflexivity; reflect on the pre-research stage in developing collaborative and negotiated design and reflect on positionality during fieldwork and data analysis to consider interpersonal and collective dynamics during the research process. Strategies are offered to harvest the benefits of the researcher's familiarity with the subject and limit any unfavorable consequences. Directions for future research include integration of research methods, using qualified Indigenous researchers, engaging Indigenous community leaders, and collecting data using native language to respect and value the culture and voice of Indigenous communities.